PREVALENCE OF PARASITES IN CRUSTACEAN AT PANMUTI BEACH, KUPANG REGENCY - Rebhung, Felix; Dahoklory, Nicodemus; Djonu, Asriati; Pasaribu, Wesly (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Crustacean catches in Panmuti Beach, including white shrimp (Litopenaeus vannamei) and swimming crab, are commodities with high economic value. This certainly increases the demand for both commodities, but the fulfillment of market needs is faced with various problems. One of them is the emergence of disease by parasite infection. The purpose of this research is to identify the types and determine the prevalence of parasites that infect these Crustaceans. Parasite identification was carried out at the Kupang Fish Quarantine, Quality Control and Fishery Product Safety Center. The sampling method uses purposive sampling. The samples observed were white shrimp (Litopenaeus vannamei) and swimming crab in live condition. The results obtained in the white shrimp sample contained one type of parasite, namely Chilodonella sp. with a prevalence of 20%. In swimming crab samples there is one type of parasite, Octolasmis sp. with a prevalence of 100%.  The results of this study can be used as information on product quality control and efforts to prevent and spread disease by parasites.